2015
DOI: 10.1002/smll.201403838
|View full text |Cite
|
Sign up to set email alerts
|

Glycocalyx‐Mimicking Nanoparticles for Stimulation and Polarization of Macrophages via Specific Interactions

Abstract: Malignant tumors develop multiple mechanisms to impair and escape from antitumor immune responses, of which tumor-associated macrophages that often show immunosuppressive phenotype (M2), play a critical role in tumor-induced immunosuppression. Therefore, strategies that can reverse M2 phenotype and even enhance immune-stimulation function of macrophage would benefit tumor immunotherapy. In this paper, self-assembled glyco-nanoparticles (glyco-NPs), as artificial glycocalyx, have been found to be able to succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 37 publications
2
71
0
1
Order By: Relevance
“…For example, macrophage reprogramming from the M1 phenotype to the M2 phenotype can be used to treat chronic inflammatory diseases [36]. The phenotypic shift of M2 macrophages toward an M1 macrophage subtype is beneficial for the early phases of inflammation and cancer immunotherapy [37]. …”
Section: Macrophage Polarizationmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, macrophage reprogramming from the M1 phenotype to the M2 phenotype can be used to treat chronic inflammatory diseases [36]. The phenotypic shift of M2 macrophages toward an M1 macrophage subtype is beneficial for the early phases of inflammation and cancer immunotherapy [37]. …”
Section: Macrophage Polarizationmentioning
confidence: 99%
“…Glycocalyx-mimicking NPs (glycol-NPs) were observed to reverse the M2 phenotype [37]. Glycol-NPs were self-assembled by three sugars, galactopyranoside (Gal), mannopyranoside (Man) and fucopyranoside (Fuc).…”
Section: Nps Modulate Macrophage Polarization and Reprogrammingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group and several others have achieved some of such mimics by using self‐assembled glyco‐containing macromolecules . Very recently, we reported that our glycocalyx‐mimicking nanoparticles (glyco‐NPs) were able to activate macrophages by turning the immunosuppressive subtype to the immunoresponsive ones, which brought forth a great potential of such glyco‐NPs in immunotherapy …”
Section: Introductionmentioning
confidence: 99%
“…11 In our previous work, we have shown that the spherical GNPs ( D n = 30–40 nm) obtained via a block copolymer self-assembly strategy were able to induce the polarization of mouse primary peritoneal macrophages from immunosuppressive phenotype to inflammatory type. 12 …”
mentioning
confidence: 99%